Exelearning como estrategia didáctica en el proceso de enseñanza-aprendizaje en la asignatura de ciencias naturales con los estudiantes de octavo año de educación general básica en la unidad educativa "Angel Polibio Chaves", cantón Guaranda, provincia Bolívar, en el periodo 2023 - 2024 - Ibarra Quinaloa, Jenifer Natali (2024)
The present research focused on the creation of digital didactic contents as an eXeLearning authoring tool in the teaching-learning process in the subject of Natural Sciences with students in the eighth year of General Basic Education at the "Angel Polibio Cháves" Educational Unit, which triggers great challenges regarding the use of technological tools. The objective was to apply eXeLearning as a didactic strategy in the teaching-learning process of the subject of natural sciences with eighth grade students in the "Angel Polibio Cháves" Educational Unit of the Guaranda canton, Bolívar province, in the period 20232024. The present research project had a mixed research approach (qualitative and quantitative) with an inductive and deductive type of research that formed a substantial part for the culmination of the technological proposal, likewise, the respective techniques and instruments were implemented for data collection consisting of a survey applied to students and a structured interview with the teacher of the “Angel Polibio Cháves Educational Unit for the analysis and measurement of the students' learning knowledge in their academic process. In the technological proposal, the instructional design of the ADDIE model was user for the creation and implementation of the contents carried out in the eXeLearning authoring tool, which was the most feasible for the application of the pretest and posttest, where it was determined that the eighth grade students' knowledge of arithmetic was low, and the intervention of this proposal confirmed the feasibility of the use made by the students, where excellent results were obtained